Carbon capture and conversion using metal-organic frameworks and MOF-based materials - Ding, Meili; Flaig, Robinson W; Jiang, Hai-Long; Yaghi, Omar M (Chemical Society reviews, 2019)
Rapidly increasing atmospheric CO 2 concentrations threaten human society, the natural environment, and the synergy between the two. In order to ameliorate the CO 2 problem, carbon capture and conversion techniques have been proposed. Metal-organic framework (MOF)-based materials, a relatively new class of porous materials with unique structural features, high surface areas, chemical tunability and stability, have been extensively studied with respect to their applicability to such techniques. Recently, it has become apparent that the CO 2 capture capabilities of MOF-based materials significantly boost their potential toward CO 2 conversion. Furthermore, MOF-based materials' well-defined structures greatly facilitate the understanding of structure-property relationships and their roles in CO 2 capture and conversion. In this review, we provide a comprehensive account of significant progress in the design and synthesis of MOF-based materials, including MOFs, MOF composites and MOF derivatives, and their application to carbon capture and conversion. Special emphases on the relationships between CO 2 capture capacities of MOF-based materials and their catalytic CO 2 conversion performances are discussed. This review summarizes recent advances and highlights the structure-property relationship on metal-organic framework-based materials for carbon dioxide capture and conversion.